Effectiveness of face masks used to protect Beijing residents against particulate air pollution. Issue 6 (9th April 2018) - Cherrie, John W; Apsley, Andrew; Cowie, Hilary; Steinle, Susanne; Mueller, William; Lin, Chun; Horwell, Claire J; Sleeuwenhoek, Anne; Loh, Miranda
Abstract : Objectives: Many residents in Beijing use disposable face masks in an attempt to protect their health from high particulate matter (PM) concentrations. Retail masks may be certified to local or international standards, but their real-life performance may not confer the exposure reduction potential that is marketed. This study aimed to evaluate the effectiveness of a range of face masks that are commercially available in China. Methods: Nine masks claiming protection against fine PM (PM2.5 ) were purchased from consumer outlets in Beijing. The masks' filtration efficiency was tested by drawing airborne diesel exhaust through a section of the material and measuring the PM2.5 and black carbon (BC) concentrations upstream and downstream of the filtering medium. Four masks were selected for testing on volunteers. Volunteers were exposed to diesel exhaust inside an experimental chamber while performing sedentary tasks and active tasks. BC concentrations were continuously monitored inside and outside the mask. Results: The mean per cent penetration for each mask material ranged from 0.26% to 29%, depending on the flow rate and mask material. In the volunteer tests, the average total inward leakage (TIL) of BC ranged from 3% to 68% in the sedentary tests and from 7% to 66% in the active tests. Only one mask type tested showed an average TIL of less than 10%, under both test conditions. Conclusions: Many commercially available face masks may not provide adequate protection, primarily due to poor facial fit. Our results indicate that further attention should be given to mask design and providing evidence-based guidance to consumers.